Climate Change, Environment and Armed Conflicts in Nigeria - Kelechi Johnmary Ani, Kelechi; Emmanuel Uwizeyimana, Dominique (International Journal of Criminology and Sociology, 2022)
Climate change has become a major cause of conflicts in Nigeria, which directly causes multiple forms of insecurity in the country. In different parts of the globe, it manifests as earth quake, hurricane, tsunami, etc. Nigeria has received its share of climate change both in two opposite forms. In the southern coastal states of Lagos, Bayelsa, and Rivers State, the ocean and overflowing waters continually threatens to wipe away the people. However, this study focuses on the north and parts of southern Nigeria, where the impact of climate change has generated armed conflict. The study which used qualitative methodology traced how climate change and the emergence of drought, famine and other forms of environmental changes leads to resource competition over land, mineral resource, water ways and by extension generating armed conflicts in many parts of Nigeria. It found that climate change caused mass migration and the settler versus non-settler conflicts that manifested in different as herdsmen-farmer conflict, as well as the armed conflict among the Ezza and her neighbours and also contributed to the Ife-Modakeke crisis in the country. Finally, the study documents multi-dimensional road-map to environmental peace and adaptations for sustainable societal development.